2009
DOI: 10.1093/ije/dyp004
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to first-line antiretroviral therapy affects non-virologic outcomes among patients on treatment for more than 12 months in Lusaka, Zambia

Abstract: Background High-level adherence to antiretroviral therapy (ART) is associated with favourable patient outcomes. In resource-constrained settings, however, there are few validated measures. We examined the correlation between clinical outcomes and the medication possession ratio (MPR), a pharmacy-based measure of adherence.Methods We analysed data from a large programmatic cohort across 18 primary care centres providing ART in Lusaka, Zambia. Patients were stratified into three categories based on MPR-calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
91
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(98 citation statements)
references
References 36 publications
5
91
2
Order By: Relevance
“…Although this effect varied according to the adherence measurement, it is evident the potential impact that non-adherence to ARV in these AIDS referral public centers has both, on the immunological recovery and on virus control. These findings are consistent with other previously published studies 31,32 . Tisson et al 33 , measuring adherence by pharmacy dispensation records, showed that the non-adherence in the initial months of treatment may result in virus failure at six and 12 months after treatment began.…”
Section: Discussionsupporting
confidence: 94%
“…Although this effect varied according to the adherence measurement, it is evident the potential impact that non-adherence to ARV in these AIDS referral public centers has both, on the immunological recovery and on virus control. These findings are consistent with other previously published studies 31,32 . Tisson et al 33 , measuring adherence by pharmacy dispensation records, showed that the non-adherence in the initial months of treatment may result in virus failure at six and 12 months after treatment began.…”
Section: Discussionsupporting
confidence: 94%
“…28 High-level adherence to antiretroviral therapy is associated with favorable patient outcomes. 29 In this study, in majority [90.42%] of encounters, >95% adherence level was reported. [ 30 The success of any adherence strategy depends on the education of patients before the initiation of ART, an assessment of their understanding of the therapy, and their readiness for treatment.…”
Section: Conflicts Of Interestmentioning
confidence: 65%
“…This could have contributed to the poorer adherence seen in men than women in our study. The majority of studies have reported no sex difference with respect to adherence [22][23][24][25][26][27], with one metaanalysis reporting a marginal association of male sex with higher adherence [16].…”
Section: Discussionmentioning
confidence: 99%